Do Labor Markets Limit the Inclusiveness of Growth in the Dominican Republic? - World Bank (World Bank, Washington, DC, 2017)
The strong economic growth enjoyed by the Dominican Republic following its 2003 domestic crisis was not matched by similarly substantial progress in poverty reduction. While labor productivity grew by an estimated 39 percent between 2000 and 2013, real wages fell with the crisis in 2003/04, and, in 2013, remained below their pre-crisis level. This report presents an assessment of factors related to the functioning of the labor markets that constrained more inclusive growth in the Dominican Republic. It explores several hypotheses related to labor supply factors, job creation, and global trends in returns to labor, as well as issues with statistical measurements that contribute to explain the weak relationship observed between growth and poverty reduction. The analysis finds that growth appears to have been driven by productivity increases rather than by increases in labor inputs. At the same time, low-skilled workers became increasingly concentrated in low-quality jobs and in sectors that saw low productivity growth, a trend enhanced by the loss of manufacturing jobs since 2000. Low rates of labor force participation, particularly among the poor, further limited the ability of households to benefit from growth.